Learning from Difference: Comparative Accounts of Multicultural Education - Lo Bianco, Joseph; Bal, Aydin (Multilingual Education, 2016)
This book analyses the experiences of multicultural education in nine very different international settings uncovering insights from a vast variety of educational contexts. Taking a multi-critical approach in reporting and discussing problems faced by increasingly multicultural and multilingual societies the nine case studies reflect radically different assumptions about what counts as ' difference' and what should be the appropriate ways for education systems to respond to differences. While each country's approach seems unique, analysis of the divergent treatments of internal population diversity elicits a genuinely global instance of the increasingly shared phenomenon of cultural pluralism. Discussing various successes and failures of policy enactment, theory, pedagogy and management of diversity, the book isolates both the differences and similarities in the unique geopolitical and socio-historical contexts of the countries investigated. A key value of the book is that it greatly expands the range of settings, experiences, epistemologies, ontologies and practical experiences that are typically encountered in mainstream discussion of what counts as 'multicultural education'. In effect, all societies are in some way 'dealing with difference' - this volume helps widen the scope of reflection and thus facilitates increased, global 'learning from difference'. .